2022
DOI: 10.1093/nutrit/nuac085
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of food away from home in low- and middle-income countries: a systematic scoping review

Abstract: Context Consumption of food away from home represents an increasing share of people’s food consumption worldwide, although the percentage of food intake that is consumed away from home varies among countries and among individuals. Previous systematic reviews have reported that, overall, consumption away from home negatively affects an individual’s diet and nutritional status. However, these reviews have mainly focused on high-income countries, leaving a gap in knowledge and data for people in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Even though the diet quality was better among individuals who reported only at-home food consumption, between the two surveys, the changes were more favourable for individuals reporting some eating away from home than for their counterparts. Food consumption away from home has been associated with higher energy and fat intake than eating at home (Lachat et al, 2012); moreover, Landais et al (2023) showed that away-from-home food consumption is associated with unfavourable effects on diet quality, nutritional status and health. Unlike this study, Bezerra et al (2021) evaluated the place of consumption considering only the first day of food record or recall in both Brazilian NDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the diet quality was better among individuals who reported only at-home food consumption, between the two surveys, the changes were more favourable for individuals reporting some eating away from home than for their counterparts. Food consumption away from home has been associated with higher energy and fat intake than eating at home (Lachat et al, 2012); moreover, Landais et al (2023) showed that away-from-home food consumption is associated with unfavourable effects on diet quality, nutritional status and health. Unlike this study, Bezerra et al (2021) evaluated the place of consumption considering only the first day of food record or recall in both Brazilian NDS.…”
Section: Discussionmentioning
confidence: 99%
“…Food consumption away from home has been associated with higher energy and fat intake than eating at home (Lachat et al., 2012); moreover, Landais et al. (2023) showed that away‐from‐home food consumption is associated with unfavourable effects on diet quality, nutritional status and health. Unlike this study, Bezerra et al.…”
Section: Discussionmentioning
confidence: 99%
“…As the recruitment started in an academic environment and, in the recruitment technique of snowball sampling, the research participants were asked to help identify other potential participants, which probably favored the dissemination of the questionnaire among academics. Another possible hypothesis would be that the consumers of food outside the home are predominantly young adults and educated, as previous studies have already identified (Bezerra et al, 2013;Landais et al, 2022;Nagao-Sato and Reicks, 2022). Furthermore, another limitation was that we examined away-from-home food consumption only at the end of Brazil's first confinement period, but habits may have changed throughout the pandemic.…”
Section: Using Of Food Servicementioning
confidence: 99%
“…52,53 The amount and frequency of consumption of food away from home (CFAFH) depends on factors such as knowledge, beliefs, advertising and social acceptance of products, eating habits, and the purchasing power of households. 54,55 Other factors such as the consumption patterns continuously fluctuate because of changes in food choice. 1,2,18,56,57 On the other hand, there has been an increase in food delivery apps that have increased the consumption of food away from home (CFAFH) 19,20 that are typically characterized for their poor nutritional quality.…”
Section: Introductionmentioning
confidence: 99%